Assessing the "social brain" in dementia: Applying TASIT-S. (August 2017) - Kumfor, Fiona; Honan, Cynthia; McDonald, Skye; Hazelton, Jessica L.; Hodges, John R.; Piguet, Olivier
Abstract: The ability to recognise how other people are feeling and make judgements based on their inferred thoughts is essential for successful social interactions, and is thought to depend on a complex network of brain regions, commonly referred to as the "social brain". These abilities, together referred to as social cognition, are increasingly recognised as being compromised in some dementia syndromes, particularly in behavioural-variant frontotemporal dementia (bvFTD), which is characterised by changes in personality and social conduct. Whether social cognition is impaired in other dementia syndromes, such as Alzheimer's disease (AD), or whether lower performance reflects general cognitive impairment, is less well established. Furthermore, ecologically valid tests with known neurobiological correlates are currently lacking. Here, we investigated performance on a newly devised short version of The Awareness of Social Inference Test (TASIT-S) and associated neural correlates in 25 bvFTD patients, 23 AD patients and 25 healthy controls. On Part 1-Emotion Evaluation, only bvFTD were impaired ( p  = .033) (AD vs. controls: p  = .475) after controlling for cognitive impairment and education. On Part 2-Social Inference, both bvFTD and AD showed intact ability to interpret sincere exchanges ( p values > .05). Importantly, however, bvFTD patients were impaired in interpreting sarcasm ( p  = .008), whereas AD performed within normal limits ( p  = .477). Voxel-based morphometry analyses demonstrated correlations between TASIT-S Part 1 performance and integrity of emotion processing brain regions (amygdala, insula, fusiform) and Part 2 performance with theory of mind brain regions (precuneus, temporal pole). These results demonstrate the utility of TASIT-S in identifying social cognition impairment in dementia and reveal that TASIT-S taps into integrity of key regions within the "social brain".